Path Analysis: The Effect of Smoking on the Risk of Periodontal Disease - Robbihi, Hilmiy Ila; Sulaeman, Endang Sutisna; Rahardjo, Setyo Sri (Indonesian Journal of Medicine, 2018)
Background: Periodontal diseases are prevalent both in developed and developing countries and affect about 20-50% of global population. Several risk factors such as smoking, poor oral hygiene, diabetes, medication, age, hereditary, and stress are related to periodontal diseases. The purpose of this study was to determine the effect of smoking on the risk of periodontal disease, using path analysis.Subjects and Method: A case-control study was carried out in Tasikmalaya community health center, West Java, from October to November 2018. A sample of 200 patients was selected by fixed disease sampling. The dependent variable was periodontal disease. The independent variables were age, knowledge on oral health, education, income, smoking behavior, oral and dental health behavior, plaque, and calculus. The data were obtained from medical record and questionnaire. The data were analyzed by path analysis.Results: The risk of periodontal disease directly increased by smoking behavior (b= 0.92; 95% CI= 0.09 to 1.75; p= 0.030), after controlling for the effect of calculus (b= 1.23; 95% CI= 0.40 to 2.07; p= 0.004) and age (b=1.63; 95% CI= 0.76 to 2.50; p<0.001). The risk of periodontal disease directly decreased by better knowledge on oral and dental health (b=-0.92; 95% CI= -1.72 to -0.12; p= 0.023) and high income (b= -1.47; 95% CI= -2.32 to -0.60; p<0.001). It was indirectly affected by plaque and education.Conclusion: The risk of periodontal disease directly increases by smoking behavior, after controlling for the effect of calculus and age. In addition, the risk of periodontal disease directly decreases by better knowledge on oral and dental health and high income. It is indirectly affected by plaque and education.Keywords: periodontal disease, smoking, factors, path analysisCorrespondence: Hilmiy Ila Robbihi. Masters Program in Public Health, Universitas Sebelas Maret, Surakarta, Jl. Ir. Sutami 36 A, Surakarta, Central Java 57126. Email: hilmiyilarobbihi@gmail.com. Mobile: +628975565050.Indonesian Journal of Medicine (2018), 3(2): 99-109https://doi.org/10.26911/theijmed.2018.03.02.06